2018
DOI: 10.12688/f1000research.13350.1
|View full text |Cite
|
Sign up to set email alerts
|

Management of eight labor and delivery patients dependent on buprenorphine (Subutex™): A retrospective chart review

Abstract: Opioid use during pregnancy is a growing concern in the United Background States. Buprenorphine has been recommended by "The American College of Obstetrics and Gynecology" as an alternative to methadone to decrease risks associated with the use of illicit opioids during pregnancy. The partial μ-opioid agonists' unique pharmacology, including its long half time and high affinity to the μ-opioid receptor, complicates patient management in a highly kinetic, and often urgent field like obstetric anesthesia. We rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…These include IV opioid PCA, rescue IV dexmedetomidine or ketamine infusions, primary or rescue truncal blocks, and lumbar or thoracic continuous epidural infusions (local-only, local plus adjunct, and opioid-only). [26][27][28][29][30][31] The key concerns of early ambulation, titratable analgesia, and unproven benefit (after intrathecal opioids or adjuncts in this special OUD population) limit what conclusions we can draw about each of these options. 32,33 Nevertheless, the past several years have seen an increase in the ERAC and OUD discussions of multimodal strategies.…”
mentioning
confidence: 99%
“…These include IV opioid PCA, rescue IV dexmedetomidine or ketamine infusions, primary or rescue truncal blocks, and lumbar or thoracic continuous epidural infusions (local-only, local plus adjunct, and opioid-only). [26][27][28][29][30][31] The key concerns of early ambulation, titratable analgesia, and unproven benefit (after intrathecal opioids or adjuncts in this special OUD population) limit what conclusions we can draw about each of these options. 32,33 Nevertheless, the past several years have seen an increase in the ERAC and OUD discussions of multimodal strategies.…”
mentioning
confidence: 99%
“…This likely reflects the large heterogenicity between included populations (for example, MacIntyre et al’s inclusion of thoracic and orofacial surgery) and therefore meaningful comparisons cannot be made. However, notably, the choice of PCA opioid varies between the MacIntyre et al (2013) cohort (morphine or fentanyl) and the preference for hydromorphone demonstrated in this audit and other case reports (Tith et al 2018). For BUP patients, although there are theoretical considerations regarding the preference for high affinity opioids like hydromorphone, there is currently no clinical evidence to support a particular opioid choice (Buresh et al 2020, Veazie et al 2020).…”
Section: Discussionmentioning
confidence: 76%
“…11 Other reported strategies for post-cesarean delivery analgesia in patients with OUD include IV PCAs, IV dexmedetomidine or ketamine infusions, regional anesthesia, and continuous epidural local anesthetic infusions with or without clonidine. [6][7][8][9][10][11][12] For her first cesarean delivery, the patient, in this case, did have a continuous lumbar epidural infusion (0.0625% bupivacaine, fentanyl 4mcg/mL) continued for 18-hrs postdelivery. This strategy provided effective pain relief while the epidural was in place, but it limited her ability to ambulate and early mobilization after cesarean delivery is generally recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have described intravenous (IV) patientcontrolled analgesia (PCA), IV ketamine and dexmedetomidine infusions, and continuous epidural local anesthetic infusions with and without clonidine for post-cesarean delivery analgesia. [6][7][8][9][10][11] Regional truncal blocks (transversus abdominis plane, quadratus lumborum and ilioinguinal-iliohypogastric blocks) or surgeon wound infiltration have also been suggested as a potentially beneficial part of multi-modal post-cesarean delivery analgesia, though no studies have been specifically performed in OUD patients undergoing cesarean delivery. 11,12 We present the novel technique of using continuous epidural hydromorphone infusion for post-cesarean analgesia in a patient with OUD maintained on daily methadone, and compare her daily opioid use, self-reported pain scores, and length of hospitalization to her first cesarean delivery in order to highlight the potential analgesic benefits of post-operative epidural hydromorphone infusion compared to standard management.…”
Section: Introductionmentioning
confidence: 99%